Pengembangan Media Pembelajaran Berbasis Google Sites dengan Model PBL untuk Meningkatkan Hasil Belajar Kognitif IPAS Siswa Kelas IV Sekolah Dasar - Widodo. A; Endang Widi Winarni; Neza Agusdianita (UNIB Press, 2026)
The purpose of this study was to develop a Google Sites-based learning media product with a PBL model to improve the cognitive learning outcomes of fourth-grade elementary school students in science. The type of research used was Research and Development (R&D) with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The data used were quantitative and qualitative data. Quantitative data were obtained from the results of validation by material, language, and media experts, product trials, and effectiveness tests through pretests and posttests. Qualitative data were obtained from the results of interviews, observations, and questionnaires of teacher and student responses. The results showed that the Google Sites-based learning media with the PBL model developed according to the material, language, and media expert validators was declared suitable for use. Teacher and student responses were categorized as very positive regarding the appearance and ease of use of the media. In addition, the results of the effectiveness test showed an increase in students' cognitive learning outcomes with an N-Gain Score of 0.7574 which is included in the high category. Based on these results, it can be concluded that the Google Sites-based learning media with the PBL model is effective for improving the cognitive learning outcomes of fourth-grade elementary school students.